2020
DOI: 10.3390/ijms21082744
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Diabetes and Alzheimer’s Disease—In the Hunt for Biomarkers

Abstract: The brain is an organ in which energy metabolism occurs most intensively and glucose is an essential and dominant energy substrate. There have been many studies in recent years suggesting a close relationship between type 2 diabetes mellitus (T2DM) and Alzheimer's disease (AD) as they have many pathophysiological features in common. The condition of hyperglycemia exposes brain cells to the detrimental effects of glucose, increasing protein glycation and is the cause of different non-psychiatric complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 146 publications
0
9
0
Order By: Relevance
“…The discovery of brain-specific insulin signaling deficit and insulin resistance in AD pathogenesis has led to the recent denomination of AD as “Type-3-Diabetes” ( Kandimalla et al, 2017 ; Leszek et al, 2017 ; Tt et al, 2020 ). Several recent studies have investigated and reviewed peripheral biomarkers common to both diseases with promising results ( Movassat et al, 2019 ; Kubis-Kubiak et al, 2020 ; Pekkala et al, 2020 ; Pereira et al, 2021 ). However, although extensive research has been conducted to understand underlying biological mechanisms that link AD and diabetes, the vast majority of evidence is based on animal models and observational clinical studies.…”
Section: Future Directionsmentioning
confidence: 99%
“…The discovery of brain-specific insulin signaling deficit and insulin resistance in AD pathogenesis has led to the recent denomination of AD as “Type-3-Diabetes” ( Kandimalla et al, 2017 ; Leszek et al, 2017 ; Tt et al, 2020 ). Several recent studies have investigated and reviewed peripheral biomarkers common to both diseases with promising results ( Movassat et al, 2019 ; Kubis-Kubiak et al, 2020 ; Pekkala et al, 2020 ; Pereira et al, 2021 ). However, although extensive research has been conducted to understand underlying biological mechanisms that link AD and diabetes, the vast majority of evidence is based on animal models and observational clinical studies.…”
Section: Future Directionsmentioning
confidence: 99%
“…Therefore, the chances of the release of ROS will be greater in the brain than in other organs. Elevated oxidative stress by different mechanisms causes neuronal cell loss and neurodegeneration [86][87][88]. Oxidative stress plays a crucial role in the development of T2D-mediated Alzheimer's pathology.…”
Section: Shared Links Between Diabetes and Ad Pathologymentioning
confidence: 99%
“…T2DM and AD have been known to share several pathophysiological features including hyperglycemia leading to increased Aβ production, and impaired glucose transport and subsequent glucose metabolism [52]. A new potential AD biomarker, S100B, has been investigated to learn the common pathophysiology of these diseases [53]. A cross-sectional study conducted with 100 South Indian AD patients showed that elevated levels of S100B protein in serum were significantly associated with clinical dementia rating scores compared to healthy controls [54].…”
Section: Links Between Gut Microbiome Composition and Ad And Associated Co-morbiditiesmentioning
confidence: 99%